2022
DOI: 10.3389/fvets.2022.1022972
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis identifies potential ferroptosis-related genes of hypoxia adaptation in yak

Abstract: There are studies on the hypoxia adaptation in yak, but there are few studies on the regulation of ferroptosis by hypoxia. This study was the first time to explore ferroptosis-related genes about hypoxia in yak. In this study, the oviduct epithelial cells between yak and bovine are performed by integrative analysis for functions, regulating network and hub genes. The results showed 29 up-regulated ferroptosis genes and 67 down-regulated ferroptosis genes, and GO-KEGG analysis showed that up-regulated different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…A recent study suggested that hypobaric hypoxia at high-altitude induces both apoptosis and ferroptosis via the JNK signaling pathway by depleting keratin 18 (Krt18) and elevating JNK3 (MAPK10), as well as increasing ASCL4 for ferroptosis [ 136 ]. An integrative comparison of the oviduct epithelial cells between yak at high altitude and bovine suggested that the mitophagy-animal pathway and HIF-1 signaling pathway may also be involved in high-altitude-induced ferroptosis [ 137 ].…”
Section: The Mechanism and Regulation Of Ferroptosis Modulated By Hyp...mentioning
confidence: 99%
“…A recent study suggested that hypobaric hypoxia at high-altitude induces both apoptosis and ferroptosis via the JNK signaling pathway by depleting keratin 18 (Krt18) and elevating JNK3 (MAPK10), as well as increasing ASCL4 for ferroptosis [ 136 ]. An integrative comparison of the oviduct epithelial cells between yak at high altitude and bovine suggested that the mitophagy-animal pathway and HIF-1 signaling pathway may also be involved in high-altitude-induced ferroptosis [ 137 ].…”
Section: The Mechanism and Regulation Of Ferroptosis Modulated By Hyp...mentioning
confidence: 99%